The Influence of Articulate Storyline media on fifth-grade elementary students’ interest in learning natural sciences - Maizura Maizura; Muhamad Nukman (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study aims to determine the effectiveness of using Articulate Storyline in increasing students' learning interest in science subjects. Articulate Storyline is an interactive digital learning tool that resembles PowerPoint but offers more advanced features and aligns with current technological developments. This study uses a quantitative, pre-experimental design. The research sample consisted of 30 fifth-grade students of SDN 161 Pekanbaru in the 2024–2025 academic year. Data collection techniques used documentation and questionnaires to measure the level of student learning interest. Data were analyzed using validity and reliability tests, as well as prerequisite tests such as normality, linearity, and hypothesis testing. The results showed that using Articulate Storyline increased students' interest in learning. Presenting material with systematic narratives and attractive visuals has been proven to motivate students in the learning process. Statistical analysis showed a significance value (Sig.) of <0.05, indicating a significant difference in learning interest after using this media. Thus, Articulate Storyline has been proven effective as a learning medium that can increase students' interest in learning. It is hoped that this learning media can be applied in subsequent learning. Abstrak Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan Articulate Storyline dalam meningkatkan minat belajar peserta didik pada mata pelajaran IPA. Articulate Storyline adalah perangkat pembelajaran digital interaktif yang menyerupai PowerPoint, namun memiliki fitur yang lebih canggih dan sesuai dengan perkembangan teknologi saat ini. Penelitian ini menggunakan pendekatan kuantitatif dengan desain eksperimen jenis pre-experimental design. Sampel penelitian terdiri dari 30 peserta didik kelas V SDN 161 Pekanbaru tahun ajaran 2024–2025. Teknik pengumpulan data menggunakan dokumentasi dan angket untuk mengukur tingkat minat belajar murid. Data dianalisis menggunakan uji validitas, reliabilitas, serta uji prasyarat seperti uji normalitas, linearitas, dan pengujian hipotesis. Hasil penelitian menunjukkan bahwa penggunaan Articulate Storyline memberikan pengaruh positif terhadap peningkatan minat belajar murid. Penyajian materi dengan narasi yang sistematis dan visual yang menarik terbukti mampu memotivasi murid dalam proses pembelajaran. Analisis statistik menunjukkan nilai signifikansi (Sig.) kurang dari 0,05, yang berarti terdapat perbedaan signifikan dalam minat belajar setelah penggunaan media tersebut. Dengan demikian, Articulate Storyline terbukti efektif sebagai media pembelajaran yang dapat meningkatkan minat belajar peserta didik. Media pembelajaran ini diharapkan dapat diterapkan pada pembelajaran selanjutnya. Kata Kunci: articulate storyline; ilmu pengetahuan alam; minat belajar; sekolah dasar